PERSEPSI WISATAWAN TERHADAP OBYEK WISATA PANTAI ANYER DI PROVINSI BANTEN - Iwan Sugiwa (Universitas Mercu Buana, 2018)
Tourism in Banten Province becomes one of the original source of income, where Banten is famous for its many beaches and religious tourism destinations. Anyer Beach is one of the famous beach attractions in Banten Province. Tourists who will visit a tourist attraction will collect information about the location to be addressed, that's when awakened an expectation and perception by potential tourists about a tourist attraction. Information gathered by tourists will help the traveler in creating a negative and positive perception. Expectations and perceptions built by tourists based on the information collected are very important in helping managers of tourism to improve the quality of tourism. Tourists who have visited a tourist attraction will compare the information obtained with the actual conditions in the location of the object. Conformity between expectations and the perception of tourists while visiting a tourist attraction will build a positive perception of a tourist attraction.